2001
DOI: 10.1084/jem.194.7.1013
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 15 Skews Monocyte Differentiation into Dendritic Cells with Features of Langerhans Cells

Abstract: Langerhans cells (LCs) represent a subset of immature dendritic cells (DCs) specifically localized in the epidermis and other mucosal epithelia. As surrounding keratinocytes can produce interleukin (IL)-15, a cytokine that utilizes IL-2Rγ chain, we analyzed whether IL-15 could skew monocyte differentiation into LCs. Monocytes cultured for 6 d with granulocyte/macrophage colony-stimulating factor (GM-CSF) and IL-15 differentiate into CD1a+HLA-DR+CD14−DCs (IL15-DCs). Agents such as lipopolysaccharide (LPS), tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
218
4
3

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 243 publications
(240 citation statements)
references
References 24 publications
15
218
4
3
Order By: Relevance
“…We have previously shown that monocytes yield DCs with Langerhans cell (LCs) properties when cultured with GM-CSF and IL-15 (25). In this study, we show that in the presence of fibroblasts and TNF, monocytes yield CD1a ϩ DC-SIGN ϩ cells as well as a subset of cells expressing surface Langerin, a marker of LCs.…”
Section: Discussionmentioning
confidence: 55%
“…We have previously shown that monocytes yield DCs with Langerhans cell (LCs) properties when cultured with GM-CSF and IL-15 (25). In this study, we show that in the presence of fibroblasts and TNF, monocytes yield CD1a ϩ DC-SIGN ϩ cells as well as a subset of cells expressing surface Langerin, a marker of LCs.…”
Section: Discussionmentioning
confidence: 55%
“…We and others have recently shown in mice the potency of IL-15-induced DC to generate OVA-specific immunity in vivo [30][31][32]. Furthermore, we showed that human IL15-DC were particularly efficient at activating Flu matrix peptide-specific memory CD8 + T cells [14]. The importance of the current work stems from the demonstration of efficient priming of CTL specific to self antigens expressed by tumor cells.…”
Section: Discussionmentioning
confidence: 68%
“…The value of this vaccine might be related to its composite nature as it consists of at least two DC subsets and most particularly Langerhans cells which have not been assessed in any other clinical trial to date. In this context, we reported that IL-15 together with GM-CSF induces monocytes to differentiate into cells with properties of Langerhans cells (IL15-DC) and the preferential ability to enhance CD8 + T cell proliferation [14]. We show here the efficiency of these cells to prime naive CD8 + T cells to differentiate into melanoma-specific CTL.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…As a control, a portion of DCs were incubated with Alexa Fluor 647-labeled L. acidophilus strains on ice. These cells were then washed with cold PBS/0.1% FCS and analyzed by flow cytometry (45).…”
Section: Expression Of Recombinant B Anthracis Pa-dc Peptide Fusion mentioning
confidence: 99%